A new model of fractional Casson fluid based on generalized Fick's and Fourier's laws together with heat and mass transfer - Sheikh, N.A. (Elsevier B.V., 2020)
A new technique for modelling the fractional model of Casson fluid is used. More exactly, the Caputo fractional model has been developed using the generalized Fick's and Fourier's laws. The magnetohydrodynamics free convection flow of Casson fluid in a channel has been considered. A new transformation is applied to the energy and mass equations and then solved by using the Laplace and Fourier sine transformations jointly. The final solutions are presented in terms of special function, namely, the Mittag-Leffler function. The effects of various physical parameters have been portrayed in graphs and tables and discussed. Â© 2019 Faculty of Engineering, Alexandria University